2017
DOI: 10.1063/1.4977844
|View full text |Cite
|
Sign up to set email alerts
|

Honey bees (Apis mellifera ligustica) swing abdomen to dissipate residual flying energy landing on a wall

Abstract: Whether for insects or for aircrafts, landing is one of the indispensable links in the verification of airworthiness safety. The mechanisms by which insects achieve a fast and stable landing remain unclear. An intriguing example is provided by honeybees (Apis mellifera ligustica), which use the swinging motion of their abdomen to dissipate residual flying energy and to achieve a smooth, stable, and quick landing. By using a high-speed camera, we observed that touchdown is initiated by honeybees extending their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…From the controls perspective, smooth landing on such diverse substrates requires insects to rapidly sense and adaptively respond to the approaching objects. While landing, insects typically decelerate [49], extend their legs [13,6,8,10,11], and align their body parallel to the substrate [2,12]. Previous studies have suggested that landing behaviors can be subdivided into these distinct, independently-activated ‘modular’ behaviors [8] that must be mutually coordinated by their nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…From the controls perspective, smooth landing on such diverse substrates requires insects to rapidly sense and adaptively respond to the approaching objects. While landing, insects typically decelerate [49], extend their legs [13,6,8,10,11], and align their body parallel to the substrate [2,12]. Previous studies have suggested that landing behaviors can be subdivided into these distinct, independently-activated ‘modular’ behaviors [8] that must be mutually coordinated by their nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously suggested that landing behavior can be subdivided into many distinct, independently-activated behaviors, and may therefore be considered as ‘modular’ (van Breugel and Dickinson, 2012). While landing, insects typically reduce their approach velocities (Baird et al, 2013; Lee et al, 1991; Lee et al, 1993; Srinivasan et al, 2000; van Breugel and Dickinson, 2012; Wagner, 1982), extend their legs (Goodman, 1960; Evangelista et al, 2010; Hyzer, 1962; Lee et al, 1993; Reber et al, 2016a; Reber et al, 2016b; van Breugel and Dickinson, 2012), and align their body parallel the landing surface (Hyzer, 1962; Zhao et al, 2017). Moreover, insects land on objects of different textures, flexibility, and orientations including inverted surfaces (Evangelista et al, 2010; Hyzer, 1962; Reber et al, 2016a), suggesting a great degree of adaptability of their landing behavior.…”
Section: Introductionmentioning
confidence: 99%
“… Taylor et al (2013) established a model to predict the abdomen response based on the non-linear combinations of air speed and optic flow. In addition, swinging motion of the honey bee abdomen was used to dissipate residual flying energy while landing ( Zhao et al 2017a ). Furthermore, Zhao et al (2015 , 2016 ) revealed the bending mechanism of honey bee abdomen and illustrated the importance of the folded intersegmental membrane (FIM) in honey bee abdominal motions.…”
mentioning
confidence: 99%